Coming to Our Senses: From the Birth of the Curator Function to Curating Live Arts. Issue 1 (1st March 2022) - McKeon, Ed
Abstract: In order to grasp the significance and potential of live arts curating, I claim it is essential to understand the coming-to-visibility of the curator function in the artworld from the 1960s. This helps to navigate the question of whether the arrival of this discourse and practice for performance in the last decade is an extension of a curatorial remit founded in the gallery arts. Has the scope of curatorial work expanded, or is there a parallel operation for live arts? I argue that a third possibility remains, that it signals a mutation of curatorial practice that bears on both the formerly visual arts and on the shifting ground of live arts. What becomes possible when curatorial work lays aside its visual privilege, its expert eyes and the authority of its insights?